Should Reductive Physicalists Reject the Causal Argument?. (7th November 2017) - Saad, Bradford
Abstract: Reductive physicalists typically accept the causal argument for their view. On this score, Tiehen (2015) parts ways with his fellow reductive physicalists. Heretically, he argues that reductive physicalists should reject the causal argument. After presenting Tiehen's challenge, I defend the orthodoxy. Although not myself a reductive physicalist, I show how reductive physicalists can resist this challenge to the causal argument. I conclude with a positive suggestion about how reductive physicalists should use the causal argument.